MULTIKULTURALISME DI BIMA PADA ABAD X – XVII - Sulistyo, Bambang (History Department, Semarang State University and Historian Society of Indonesia, 2014)
The authors tend to argue that the history of Bima, in West Nusatenggara was started in early 17th century, when Bima development political relations with South Sulawesi. Hindu civilization in the form of worship in Wadu Paha, be overlooked, was regarded as a foreign culture. Historians tend to argue that Bima before Islam, have animism and dynamism belief. There are tendency rejects reality the Javanese role in history of Bima.This argument is not rational. What is the benefit of foreigner build a place of worship in one community who has different beliefs? This article would reconstruction history of Bima with appreciate the various components of culture that shaped his civilization. Elements of pre- Islamic became an important civilization component; not only animism and dynamism, but also Hindu . It is still apparent as the idealism of Bimanese in the present.Keywords: multiculturalism, ethnic, BimaPara penulis sejarah Bima berpendapat bahwa awal peradaban Bima dimulai pada abad 17, ketika Bima menjalin hubungan-hubungan politik dengan Sulawesi Selatan. Peradaban Hindu berupa kompeks peribadatan di Wa du Paha, cenderung diabaikan, dianggap sebagai kebudayaan asing. Para sejarawan cenderung berpendapat bahwa Bima sebelum Islam, memiliki kepercayaan animisme dan dinamisme. Ada kecenderungan subyektivitas yang menolak peran Jawa dalam sejarah Bima. Namun apabila dicermati pendapat ini tidak rasional. Apa kepentingan orang Asing membangun tempat peribadatan di suatu komunitas yang memiliki kepercayaan yang berbeda. Tulisan ini berupaya merenkonstruksi kembali sejarah Bima dengan menempatkan dan menghargai berbagai komponen kebudayaan Bima yang telah membentuk peradabannya. Unsur-unsur pra Islam menjadi unsure penting peradaban tidak hanya animism dan dinamisme, tetapi juga Hindu. Hal ini masih nampak jelas sebagai idealism orang Bima di masa kini.Kata kunci: multikulturalisme, etnis, Bima